Practical reflectivity as a context for teachers´ professional development: a mixed-methods study - Coimbra, Maria Nazaré; Martins, Alcina Oliveira; Pinto, Isabel Pereira; Duarte, Rosa Serradas (Advances in Social Sciences Research Journal, 2014)
This study aims at analysing the influence of practical reflectivity, as a context for professional learning, and its impact on teaching practices. Therefore, a mixed research method has been selected, based on qualitative and quantitative procedures, combining an enquiry to high school teachers and interviews to supervisors, given their privileged knowledge on the educational reality of schools and especially on the performance of teachers in classroom. These two areas of analysis, in spite of being different in terms of methodological nature, enable a comparative analysis. The study shows that all the participants, teachers and supervisors, recognize the importance of a contextualized reflection-in-action as the means to achieve greater quality of practices and an effectiveness of professional teaching development. It is also consensual the importance of a reflective teacher, who is able to question and improve his practice using investigation-in-action as basis. However, reflection is not always applied during the educational process, demanding more collaborative work between peers, pedagogical didactic update and investigation placing the student as centre. Although there is still a long way to go in terms of professional training, participants of this study perceive reflectivity as the right way to be a teacher in an educational community.